Indonesia - Mohammad Rafli; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2023)
Comparative law is the activity of comparing laws from various countries, the purpose of which is to contribute to the development of new laws and regulations or their amendments and find how similarities and differences in concepts, legal institutions that contribute, legal systems used. In Indonesia, land law is regulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, hereinafter referred to as UUPA, while in Russia land law is regulated in The Land Of Code Russia No. 136-FZ of 2001. The formulation of this research problem is how are the similarities and differences in the regulation of buying and selling land in Indonesia and Russia, the research method uses normative juridical type, the nature of descriptive research is sourced from secondary data, the research data is analyzed qualitatively and the conclusion is drawn using deductive. In addition, there are differences in the sale and purchase of land in Indonesia and Russia, namely the regulation of land sale and purchase, the meaning of land, the object of land sale and purchase, the transfer of rights from the seller to the buyer, the initial agreement, the parties authorized to make the agreement.